1974
DOI: 10.2307/2441629
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Cytology of Tilletia caries and T. controversa in Axenic Culture

Abstract: On a wheat-based medium, the pathogenic phase of the common and dwarf bunt fungi grew slowly at 15-18 C and continued to produce massive quantities of teliospores in all subcultures for over 2 years. At warmer temperatures or on a chemically defined medium, the teliosporogenic colonies reverted to haploid mononucleate colonies. The hyphae of the teliosporogenic colonies were stained with a modified Giemsa technique and found to be thick, contorted, highly branched and short celled with usually one or two nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…could also be a good candidate, but its teliospores are larger [ca. 16-24 µm (Trione 1974;Pimentel et al 2000;Župunski et al 2012)] so this would be di cult unless the specimen photographed was quite immature, which is not probable. It is rather unlikely that this last type of spores belongs to Puccinia Pers., a genus that commonly infects wheat, causing rust.…”
Section: Fungal Sporesmentioning
confidence: 99%
“…could also be a good candidate, but its teliospores are larger [ca. 16-24 µm (Trione 1974;Pimentel et al 2000;Župunski et al 2012)] so this would be di cult unless the specimen photographed was quite immature, which is not probable. It is rather unlikely that this last type of spores belongs to Puccinia Pers., a genus that commonly infects wheat, causing rust.…”
Section: Fungal Sporesmentioning
confidence: 99%
“…In axenic culture, Trione (53) found that the vegetative hyphae of T. caries and T. controversa had the same morphology. However, enzymatic studies of the teliospores of these two species suggested that there are some definite differences.…”
Section: Biochemical Identificationmentioning
confidence: 99%